Choledochal cyst perforation: experience from a centre with limited emergency resources - Jadhav, Amitkumar; Chakraborty, Goutam; Sugandhi, Nidhi; Acharya, Sameer Kant (International Journal of Contemporary Pediatrics, 2021)
Spontaneous perforation in Choledochal cyst (CDC) is a very rare initial manifestation and more commonly seen beyond infantile age. The management is challenging due to acute presentation, poor general condition of the patient and inflamed tissue that may jeopardize the appropriateness of any surgical intervention. The aim of the study was to analyse this rarity depending on clinical findings, diagnostic difficulty and optimum management plan in a limited resource set-up. It was a retrospective observational study where five patients presenting to the casualty department with biliary peritonitis between January 2015 and December 2020 were included. They were analysed with respect to symptomatology, laboratory parameters, radiology, emergency intervention with findings and definitive management plan. A female preponderance (60%) was found. Mean age was 5.4 years. One was a known case of CDC. Abdominal pain was the most common symptom. Inflammatory markers like Total leucocyte count (TLC) and Erythrocyte sedimentation rate (ESR) were raised in all (100%). Lipase was raised in 40% (2/5). Anaemia and low serum albumin were non-specific findings. A dilated Common bile duct (CBD) on Ultrasound (US) was seen in 80% (4/5). Magnetic resonance cholangio pancreaticography (MRCP) demonstrated type I CDC in all. All underwent laparotomy with lavage and external drainage followed by interval definitive surgery. Pre-operative diagnosis of a perforated CDC may not be possible. Strong clinical suspicion and bilious peritoneal fluid may point to this rare complication. Minimum exploratory manoeuvre with good lavage and external drainage should be the optimum emergency intervention. Definitive bilio-pancreatic reconstruction should be performed when tissue oedema subsides and general condition is improved. This approach usually achieves a rewarding outcome.